(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Free living amoeba (FLA) are widely distributed in various environmental sources and they have been found world-wide in aquatic habitats, soil and air.This study was performed in Thi –Qar province south of Iraq in order to detection of the opportunistic FLA in water samples and identified by morphological characters in the culture .During the period from November 2021 to February 2022 forty samples of water were collected ,All samples were cultured in the NN-agar medium and then examined by light microscope and we recognized morphologically the trophozoites and cysts of opportunistic amoebas that belong to the genera ; Naegleria fowleri. ,Acanthamoeba spp , Sappinia spp and Balamuthia mandrillaris , the study found 27(67.5%) samples were positive for total opportunistic FLA , and 13(32.5%) samples were negative , Where Sappinia spp. was the most common amoeba in water samples while Naegleria fowleri was less present